PERAN KEPEMIMPINAN PENDIDIKAN TERHADAP BUDAYA ADMINISTRASI DAN MANAJEMEN KEARSIPAN DI SEKOLAH - Faizatul Ilmi; Ulya Abdillah Ramadhani; Fadilah Aditya; Adirani Nur Azizah; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of educational leadership in developing an effective administrative culture and improving records management in schools. Educational leadership plays a strategic role in directing, controlling, and developing school administrative systems, including systematic and sustainable records management. The method used is a qualitative approach through library research by reviewing various literature related to educational leadership, administrative culture, and records management. The findings indicate that visionary, participatory, and value-based leadership can foster a disciplined, transparent, and accountable administrative culture. Furthermore, effective leaders contribute to developing technology-based archival systems, enhancing administrative staff competencies, and ensuring sustainable document management. Therefore, the success of records management in schools is highly influenced by the quality of educational leadership. Keywords: educational leadership, administrative culture, records management, school, educational governance